Efeito osteogênico do compósito produzido com cerâmica de beta tricálcio fosfato, polímeros [PCL e PLGA] E β-ciclodextrina, associado à doxiciclina, no modelo de reparo ósseo alveolar em ratos - Bruno Sérgio Bahia Lopes (2019)
The evaluation of the osteogenic potential, in an animal bony model after tooth extraction, it was made for a composite containing calcium phosphate bioceramics, biodegradable polymers, and an antimicrobial agent, doxycycline, of the tetracycline class. The newly formed bone was qualitatively characterized (histologically) and quantitative (histomorphometrically). The animals were divided into 04 groups: Group 01 (Blood Clot – Control), Group 02 (βTCP – Control), Group 03 (βTCP/PCL/PLGA – Control) and Group 04 (βTCP/PCL/PLGA/DOX/βCD – Test). After left upper molar extraction, and alveolar bone defect was prepared. A single surgical store was created, and filled with the material corresponding to each group. After predetermined times, T1 (14 days) and T2 (28 days) proceeded with the proposed analysis. Histological analysis showed, for all groups, the presence of neoformed bone at both times, and at T1, Group 04 – Test, obtained the largest área of the neoformed bone when compared to the other groups. Group 04 – Test, kept the volume practically stable between times, and a slight increase can be observed, but with much more mature and structured trabeculated bone in T2. When observing the inflammatory infiltrate, it was noted that it was predominantly mononuclear, compatible with the repair process, for all groups, and the βTCP/PCL/PLGA/DOX/βCD group, this infiltrate was slightly decreased. The histomorphometric analysis confirmed the qualitative histological findings. For the 14 days time, the Test Group presented the largest measured área of newly formed bone (47%), when compared to Group 01 (36%), Group 2 (33%) and Group 03 (31%), with no statistical difference between the times compared into the same groups or between groups, when compared different groups (p<0,05). The osteoclast immunostaining (TRAP) also showed a smaller amount of these cells in Group 04 – Test with 28 days, when compared with the same group with 14 days, evidencing the antiosteoclastogenic effect of DOX. It was concluded, therefore, that Doxycycline used in the controlled drug delivery system was able to increase the quality and speed of bone neo-formation for this experimental model, especially in the critical early stages of bone repair (T1 – 14 days). This composite has promising use for clinical applications related to the maintenance of the alveolar bone ridge.